15.8k views
0 votes
Factor 25m squared - 10m + 1

User Zrabzdn
by
5.2k points

1 Answer

3 votes

Given:


25m^2-10m+1

Let's factor the expression.

To factor the expression, first rewrite 5² = 25:


\begin{gathered} 5^2m^2-10m+1 \\ \\ (5m)^2-10m+1 \end{gathered}

Now, rewrite 1² = 1:


(5m)^2-10m+1^2

Now, check that the middle term is two times the product of the first term being squared (5m) and the last term (1).

We have:

2 x (5m x 1) = 10 m

Thus, we have the expression:


(5m)^2-2*5m*1+1^2

Now, factor using the Perfect Square Trinomial rule:


a^2-2ab+b^2=(a-b)^2

Thus, we have:


(5m)^2-2*5m*1+1^2=(5m-1)^2

Where:

• a = 5m

,

• b = 1

Therefore, the factored form of the given expression is:


(5m-1)^2

ANSWER:


(5m-1)^2

User Samuel Kim
by
4.7k points